O direito à saúde: a medida do dever do estado de fornecer Medicamentos de dispensação excepcional à sociedade sob a ótica do desenvolvimento - Ermel, Regina Mariana Araújo (2008)
It is a fact that the fundamental rights of citizens are being recognized and guaranteed by the state over time, regardless of the belief that if these rights has always been part of the heritage of subjective individuals, or whether they will be aggregated during the course of human history. In that, emerged the rights of freedom of men and, subsequently, the rights to create a situation of equality between the humans, the so-called social rights. In turn, as these rights known as social, to be implemented, need a positive action by the state, more precisely by the state power whose function is to manage public money and create policies for implementation of fundamental rights. Given this, pay attention to the right to health, was created the Programa de Medicamentos de Dispensação Excepcional, which aims to provide high-cost medicines to citizens Brazilian carriers of serious diseases, such as Alzheimer's and Mal Hepatitis C. Also on the program, it provides a way which will be mandatory that the drugs will be offered in such situations, and does not include a means of updating the list predicted able to monitor the progress of medicine that have been in the interest of the program. Given that, at present it is necessary to mention the recognition of another fundamental right: the right to development, which is the right of access to positive actions being implemented by the State, which are nothing more than public policy, gender which the Programa de Medicamentos de Dispensação Excepcional is kind. Thus, through the search in legislation and doctrine in relation to the theme, this work has the aim to examine the extent of the state to provide exceptional dispensing of medicines. Specifically, if the State in attention to the right to development and the implementation of the right to health, can really list exhaustively the drugs to be provided by the State, and what are the elements guiding this choice and how to control the same